Damages to wooden houses caused by xylophagus Coleoptera, IX Region, Chile - Rebolledo R., Ramón; Sáez B., Patricio; Klein K., Carlos; Salas E., Cristián; Aguilera P., Alfonso (Bosque (Valdivia), 2006)
In Padre Las Casas in the IX Region of La Araucanía, wood buildings have serious deterioration problems caused by xylophages Coleopteran producing structural and aesthetic damage. In this survey, subterranean termites were not found. In four different sectors of the city, the damage was evaluated in 98 houses randomly sampled, in which the damage was quantified and the relationship damage-age was established. The total built surface, the presence or absence of damage, type of wood damaged, degree of elaboration and level of deterioration were estimated. Wooden parts with symptoms of damage caused by adult insects were collected for later laboratory studies and for species identification. A total of 71 houses presented damage (70% of the total), being the sector Villa los Canelos the most affected, with 89%. Structural exotic wood presented the highest damage with 54%, followed by its combination with native ones with 14%; native wood showed only 2% of damage. Painted wood presented 44% of damage, due mainly to its age in most houses. The species associated to wood in service were the common furniture beetle Anobium punctatum Hadrobregmus punctatipennis and the wood-boring weevil Pentarthrum huttoni.